Clinical Evaluation of a Novel Electromechanical Topical Ocular Drug Delivery System: Two Phase 1 Proof of Concept Studies - Quiroz-Mercado H (Dove Medical Press, 2020)
Hugo Quiroz-Mercado, 1 Ehud Ivri, 2 Roberto Gonzalez-Salinas, 1 Iraklis C Kourtis, 2 Joseph Gilbert, 2 José Francisco Pérez-Vázquez, 1 Mark Blumenkranz, 2 Jesús Jiménez-Román, 1 George Marcellino 2 1Association to Prevent Blindness, Hospital Sanchez-Bulnes, Mexico City, Mexico; 2Kedalion Therapeutics Inc., Menlo Park, CA, USACorrespondence: Hugo Quiroz-Mercado Vicente García Torres #46, Coyoacan, CDMX CP 04330, MexicoTel/Fax +52-5-10841-400Email hugoquiroz@yahoo.comPurpose: Self-administration of topical ophthalmic therapies remains challenging for many patients as errors due to improper technique are common. The aim of the current studies was to evaluate a novel electromechanical topical ocular drug delivery device designed to facilitate precise dosing and accurate delivery with substantially lower drug exposure than conventional eye drops.Patients and Methods: Two randomized Phase 1 studies were performed to evaluate the efficacy and safety of a single dose of a topical ophthalmic solution administered as a ∼ 9 μL microfluid stream via the test device compared with a ∼ 30– 40 μL drop delivered via conventional dropper in healthy subjects (Trial 1) and glaucoma patients (Trial 2). In Trial 1, a 1% tropicamide/2.5% phenylephrine solution was administered via the test device in one eye and by conventional dropper in the contralateral eye. Pupil dilation was measured at 30 min intervals post-instillation and subject comfort was assessed using a visual analogue scale (range, 0– 100). In Trial 2, patients were randomized to receive latanoprost 0.005% via the test device or conventional dropper. Intraocular pressure was measured at baseline and 4– 8 hrs post-instillation.Results: In Trial 1 (N=20), mean (SD) pupil diameter 30 mins post-instillation increased by 3.4 (0.9) and 3.5 (1.0) mm in the test and control eyes, respectively. The mean comfort score was 81.7 for the test device versus 57.3 for conventional dropper delivery. In Trial 2 (N=18), the mean change in intraocular pressure following administration of latanoprost was – 5.0 (1.8) and – 4.3 (3.3) mm Hg in the test and control groups, respectively. No serious adverse events were observed in either study.Conclusion: Administration of a single dose of topical ophthalmic therapy via an electromechanical drug delivery device resulted in comparable effects on pupil dilation and intraocular pressure with lower drug exposure and increased patient comfort compared with conventional dropper delivery.Keywords: mydriasis, phenylephrine, tropicamide, glaucoma, intraocular pressure, latanoprost, topical ocular drug delivery, safety